Comparison of spatial patterns of ammonia concentration and dry deposition flux between a regional Eulerian chemistry-transport model and a local Gaussian plume model - Niramson Azouz; Jean-Louis Drouet; Matthias Beekmann; Guillaume Siour; Roy Wichink Kruit; Pierre Cellier (Air Quality, Atmosphere & Health, 2019)

The Role of Stakeholders in Creating Societal Value From Coastal and Ocean Observations - Bev Mackenzie; Louis Celliers; Luiz Paulo de Freitas Assad; Johanna J. Heymans; Nicholas Rome; Julie Thomas; Clarissa Anderson; James Behrens; Mark Calverley; Kruti Desai; Paul M. DiGiacomo; Samy Djavidnia; et al. (Frontiers in Marine Science, 2019)

Sensitivity of community‐level trait–environment relationships to data representativeness: A test for functional biogeography - Benjamin Borgy; Cyrille Violle; Philippe Choler; Eric Garnier; Jens Kattge; Jessy Loranger; Bernard Amiaud; Pierre Cellier; Guilhem Debarros; Pierre Denelle; Sylvain Diquelou; Sophie Gachet; et al. (Global Ecology and Biogeography, 2017)
Aim The characterization of trait–environment relationships over broad‐scale gradients is a critical goal for ecology and biogeography. This implies the merging of plot and trait databases to assess community‐level trait‐based statistics. Potential shortcomings and limitations of this approach are that: (i) species traits are not measured where the community is sampled and (ii) the availability of trait data varies considerably across species and plots. Here we address the effect of trait data representativeness [the sampling effort per species and per plot] on the accuracy of (i) species‐level and (ii) community‐level trait estimates and (iii) the consequences for the shape and strength of trait–environment relationships across communities. Innovation We combined information existing in databases of vegetation plots and plant traits to estimate community‐weighted means [CWMs] of four key traits [specific leaf area, plant height, seed mass and leaf nitrogen content per dry mass] in permanent grasslands at a country‐wide scale. We propose a generic approach for systematic sensitivity analyses based on random subsampling and data reduction to address the representativeness of incomplete and heterogeneous trait information when exploring trait–environment relationships across communities. Main conclusions The accuracy of the CWMs was little affected by the number of individual trait values per species [NIV] but strongly affected by the cover proportion of species with available trait values [ P Cover ]. A P Cover above 80% was required for all four traits studied to obtain an estimation bias below 5%. Our approach therefore provides more conservative criteria than previously proposed. Restrictive criteria on both NIV and P Cover primarily excluded communities in harsh environments, and such reduction of the sampled gradient weakened trait–environment relationships. These findings advocate systematic measurement campaigns in natural environments to increase species coverage in global trait databases, with special emphasis on species occurring in under‐sampled and harsh environmental conditions.

Modeling nitrous oxide emissions from tile-drained winter wheat fields in Central France - Jiangxin Gu; Denis Loustau; Catherine Hénault; Philippe Rochette; Pierre Cellier; Bernard Nicoullaud; Agnes Grossel; Guy Richard (Nutrient Cycling in Agroecosystems, 2014)

Determination of Levels of Current Drugs in Hospital and Urban Wastewater - Elodie Saussereau; Christian Lacroix; Michel Guerbet; Dominique Cellier; Joël Spiroux; Jean-Pierre Goullé (Bulletin of Environmental Contamination and Toxicology, 2013)

Importance of Anthropogenic Metals in Hospital and Urban Wastewater: Its Significance for the Environment - Jean-Pierre Goullé; Elodie Saussereau; Loïc Mahieu; Dominique Cellier; Joël Spiroux; Michel Guerbet (Bulletin of Environmental Contamination and Toxicology, 2012)

Carbon, nitrogen and Greenhouse gases budgets over a four years crop rotation in northern France - Benjamin Loubet; Patricia Laville; Simon Lehuger; Eric Larmanou; Christophe Fléchard; Nicolas Mascher; Sophie Genermont; Romain Roche; Rossana M. Ferrara; Patrick Stella; Erwan Personne; Brigitte Durand; et al. (Plant and Soil, 2011)

Dissolved carbon leaching from soil is a crucial component of the net ecosystem carbon balance - REIMO KINDLER; JAN SIEMENS; KLAUS KAISER; DAVID C. WALMSLEY; CHRISTIAN BERNHOFER; NINA BUCHMANN; PIERRE CELLIER; WERNER EUGSTER; GERD GLEIXNER; THOMAS GRŨNWALD; ALEXANDER HEIM; ANDREAS IBROM; et al. (Global Change Biology, 2011)
Estimates of carbon leaching losses from different land use systems are few and their contribution to the net ecosystem carbon balance is uncertain. We investigated leaching of dissolved organic carbon (DOC), dissolved inorganic carbon (DIC), and dissolved methane (CH 4 ), at forests, grasslands, and croplands across Europe. Biogenic contributions to DIC were estimated by means of its δ 13 C signature. Leaching of biogenic DIC was 8.3±4.9 g m −2 yr −1 for forests, 24.1±7.2 g m −2 yr −1 for grasslands, and 14.6±4.8 g m −2 yr −1 for croplands. DOC leaching equalled 3.5±1.3 g m −2 yr −1 for forests, 5.3±2.0 g m −2 yr −1 for grasslands, and 4.1±1.3 g m −2 yr −1 for croplands. The average flux of total biogenic carbon across land use systems was 19.4±4.0 g C m −2 yr −1 . Production of DOC in topsoils was positively related to their C/N ratio and DOC retention in subsoils was inversely related to the ratio of organic carbon to iron plus aluminium (hydr)oxides. Partial pressures of CO 2 in soil air and soil pH determined DIC concentrations and fluxes, but soil solutions were often supersaturated with DIC relative to soil air CO 2 . Leaching losses of biogenic carbon (DOC plus biogenic DIC) from grasslands equalled 5–98% (median: 22%) of net ecosystem exchange (NEE) plus carbon inputs with fertilization minus carbon removal with harvest. Carbon leaching increased the net losses from cropland soils by 24–105% (median: 25%). For the majority of forest sites, leaching hardly affected actual net ecosystem carbon balances because of the small solubility of CO 2 in acidic forest soil solutions and large NEE. Leaching of CH 4 proved to be insignificant compared with other fluxes of carbon. Overall, our results show that leaching losses are particularly important for the carbon balance of agricultural systems.

Seasonal variability of apoplastic NH4 + and pH in an intensively managed grassland - Benjamin Loubet; Celia Milford; Paul W. Hill; Y. Sim Tang; Pierre Cellier; Mark A. Sutton (Plant and Soil, 2002)